Perancangan Brand Campaign dan Media Promosi Instagram untuk Meningkatkan Awareness Brand Scentella - leticia, charissa belle (Universitas Ciputra Surabaya, 2024)
This study aims to introduce the Scentella brand to market audiences using a Brand Campaign and the use of Instagram social media as a media of promotion. Scentella is a Surabaya-based aromatherapy candle brand that sells candles made with natural ingredients. The research method used is descriptive qualitative and the subjects are Scentella followers on Instagram. The use of Instagram media as a promotional medium is the right thing nowadays. The value of the Scentella brand can be conveyed to market audiences through Instagram social media. The design style used by Scentella is Scandinavian, both in terms of color selection and the application of designs for promotional media. It is hoped that there will be increased awareness of the campaign implemented by Scentella.